Who cites whom? U.S.-American authored research syntheses in the field of educational technology: a bibliometric analysis - Buntins, Katja; Bedenlier, Svenja; Zawacki-Richter, Olaf (Learning Media and Technology, 2025)
Research syntheses are an important approach to capture and synthesize empirical studies in educational technology. However, despite their proclaimed impartial summary of available research, imbalances exist as to whose research is included due to publication language or in regard to the visibility of entire scientific communities. Using the concepts of academic hegemony and WEIRD research, a bibliometric analysis is conducted in order to explore how research syntheses of authors located in one of the so-called academic core countries–the U.S.A.–are positioned in international comparison, and how this potentially shapes the discourse on educational technology. For the bibliometric analysis, a corpus with N = 446 research syntheses is considered, comprised of 95 U.S.-authored and 351 non-U.S.-authored syntheses. Findings reveal that U.S.-authored syntheses are relatively self-referential and also draw heavily on databases of U.S.-based professional societies in their literature search. Over half of the syntheses cite other U.S.-based research, followed by Chilean, British, Canadian, Australian and German research. In contrast, U.S.-authored syntheses are cited globally, accentuating their perceived importance and influence. Findings point to the need to consider underlying influences and contextual factors for research syntheses in educational technology, reflect on citation practices and generalizability of findings from educational research.
CRIS-Team Scopus Importer:2025-05-23
Keywords: academic hegemony; bibliometric analysis; educational technology; generalizability; Research synthesis